PERLINDUNGAN HUKUM PENGETAHUAN TRADISIONAL DALAM KONSEP HUKUM KEKAYAAN INTELEKTUAL - Muthia Septarina (Al-Adl : Jurnal Hukum, 2016)
As for the objectives of this study are to find out who is the subject of law whichbecame the holder of the rights in the protect of traditional knowledge and to findout how the forms of legal protection granted to traditional knowledge thisresearch is expected to provide a significant contribution both theoritycally andpractically.This study uses research methods of socio-logical research using aninterdisciplinary approach among aspects of social logical research usingnoemaive approach who used the method of qualitative analysis is by analyzingthe data in depth and holistic as stated by David M Fettermen “this descriptionmight include the groups’s history, religion, politics, economy and environment”with another word presented the relationship between context in which is lawlocated it is o meet the need for more detailed and thorough explaination of thelegal issues in a more meaning full by making comparisons between law in bookwith law in action.